CORRELAÇÃO ENTRE O USO DE REPOSIÇÃO HORMONAL E O PERFIL LIPÍDICO DE MULHERES PÓS - Gelatti, Gabriela T.; Dezordi, Francieli P.; Oliveira, Karla R. d.; Berlezi, Evelise M. (Salão do Conhecimento, 2013)
Resumo